Nanotechnology’s Voyage: Enriching Aquafeed with Nutraceuticals - Chatterjee, Priyajit; Khan, Argha (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
The integration of nutraceuticals into aquafeed presents a promising approach to enhancing the health and growth performance of aquatic species. However, the effectiveness of these bioactive compounds is often limited by their stability, bioavailability, and delivery efficiency. Nanotechnology is a key tool in modern agriculture, and agri-food nanotechnology is expected to become a major economic force in the near future. This field focuses on sustainability and protecting foods produced through agriculture, including crops for both human consumption and animal feed. Nanotechnology offers innovative solutions to these challenges by enabling the encapsulation and controlled release of nutraceuticals, thereby improving their stability and bioavailability. This abstract explores the potential of nanotechnology in the development of advanced aquafeeds enriched with nutraceuticals. Key areas of focus include the design and synthesis of nanocarriers, such as liposomes, nanoparticles, and nano-emulsions, tailored for aquatic environments. The benefits of using nanotechnology for nutraceutical delivery in aquafeed are discussed, including enhanced nutrient absorption, targeted delivery, and sustained release, which collectively contribute to improved health and productivity of farmed aquatic species. The abstract also highlights current research trends, challenges, and future prospects in the application of nanotechnology to aquafeed, underscoring its potential to revolutionize aquaculture nutrition and support sustainable aquaculture practices.